(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1921)
The coped stone has sloping sides covered with three rows of well-defined tiles, or shield-shaped scale-like ornamentation. Along the ridge, which is flat, there is a deeply-cut channel. The stone, which is of red freestone much covered with lichen, lies due east and west, the broader end to the west. The cross-slab was found while a grave was being dug. Incised on the face is a geometrical four armed cross within a circle, the diameter of which is 10 inches. This cross is surmounted by a small equal-armed cross, the top arm being imperfect. It has a single step at the foot, and to this extent it resembles a Calvary cross. Each end of the side arms terminates in a crescent, a very unusual occurrence.